El ensamble de invertebrados y la calidad del agua: indicadores taxonómicos y funcionales en arroyos pampeanos - García, M. E. (2009)
The use of benthic invertebrates is considerate and recognized at present as one of the better methodological alternative to detect early modifications or contamination from diffuse origin. The objective of this work was to evaluate the biological quality of two regional pampean plain streams by means of taxonomic and functional indicators of the whole of invertebrates assemblages and to compare the utility of the different applied indicators. The selected streams belong to the Rio de La Plata basin, with different anthropogenic impact. Over a period of two years, the physicochemical parameters and the benthic invertebrates and those present in the vegetation, of these lotic systems were assessed in samplings sites located upstream and downstream. Taxonomic and functional feeding groups, of the invertebrate assemblages were analyzed. The estimated taxonomic indicators reflected seasonal differences and the valuation of the quality of the sites were different and variable depending on the parameter and the taxonomical level used. Even so, the density of the most abundant family, the abundance of Ephemeroptera-Trichoptera (ET), the ET/total and ET/Oligochaeta relations resulted useful to establish differences between sites and streams. The collectors appeared as the dominant functional feeding group in all the sites. No significant differences were observed in the composition of the functional feeding groups of the invertebrate assemblages from headwaters to the mouth of both streams. Then these indicators would not be efficient to evaluate the environmental quality of these systems.